APPROACHES TO TEACHING ESL ACADEMIC WRITING: A MULTIPLE CASE STUDY - Khairunnisa Azmar; Abu Bakar Razali (Malaysian Journal of Learning and Instruction, 2025)
Purpose - Academic writing skills are fundamental for students at tertiary level. Possessing these skills can aid students in their studies as they are mostly assessed based on their proficiency in writing skills. Due to this, the teaching of English academic writing has become pivotal for English as a second language (ESL) lecturers in ensuring students’ abilities to write academically, while at the same time achieving the course learning outcomes. Therefore, this study aims to explore the teaching approaches employed by ESL lecturers in teaching English academic writing at Malaysian universities.